Performance evaluation of electrostatic precipitator transformer by considering power quality - Mohammad Khakroei; Mohsen Mostafaei; Ashkan Mirzaei Rajeooni (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Electrostatic precipitators (ESPs) are industrial emission control units. The ESPs are designed to trap and remove dust particles from the exhaust gas stream by using the force of an electric field, which is produced by a high-voltage power supply. One of the main problems of these power supplies is the presence of non-linear elements that adversely affect the power quality of the system. In this paper, a transformer/rectifier (T/R) set is modeled as a high-voltage power supply for an ESP, and the distribution of electromagnetic forces on the set is analyzed using the Finite Element Method (FEM). Additionally, the current waveform and Total Harmonic Distortion (THD) of the T/R set are modified by designing and utilizing a passive filter for the system. First, the working principle and operation of the T/R set are modeled. Then, the electromagnetic design of the T/R set is evaluated by the finite element method and the transient analysis of the flux densities, and associated radial and axial components of electromagnetic forces distribution on the T/R set. Afterward, a wire-plate ESP configuration is modeled and analyzed based on the Electric potential and Electric field. Finally, the design method of the passive filter is explained, and it is shown that the utilization of the designed passive filter has significantly reduced the THD of the T/R set.